Cavitating Mesenteric Lymph Node Syndrome in Association with Coeliac Disease and Enteropathy Associated T-Cell Lymphoma: A Case Report and Review of the Literature - Olivia M. B. McBride; Richard J. E. Skipworth; Derek Leitch; Satheesh Yalamarthi (Case Reports in Medicine)
Cavitating mesenteric lymph node syndrome (CMLNS) is a rare and poorly understood complication of coeliac disease (CD), with only 37 cases reported in the literature. CD is an immune-mediated enteropathy, with alterations seen in the small bowel architecture on exposure to ingested gluten. Those who fail to respond to a strict gluten-free diet are termed to have refractory coeliac disease (RCD). This is associated with serious complications such as enteropathy-associated T-cell lymphoma (EATL). We present the case of a 71-year-old female investigated for weight loss and a palpable intraabdominal mass. Abdominal computed tomographic (CT) scan showed multiple necrotic mesenteric lymph nodes. At operation, multiple cavitating mesenteric lymph nodes, containing milky fluid, were found. An incidental EATL was found at the terminal ileum, which was resected. The patient subsequently tested positive for CD. This is the second case report to document an association between CMLNS and EATL. This paper highlights the varied presentation of CD. In this case, the diagnosis of CD was made retrospectively after the complications were dealt with. This paper is followed by a review of relevant literature.